2021
DOI: 10.3390/en14154444
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Framework for 5G Wireless System Integration into Industry 4.0 Applications

Abstract: The fourth industrial revolution, or Industry 4.0 (I4.0), makes use of wireless technologies together with other industrial Internet-of-Things (IIoT) technologies, cyber–physical systems (CPS), and edge computing to enable the optimization and the faster re-configuration of industrial production processes. As I4.0 deployments are ramping up, the practical integration of 5G wireless systems with existing industrial applications is being explored in both Industry and Academia, in order to find optimized strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 28 publications
(36 reference statements)
0
20
0
Order By: Relevance
“…Further advances in 5G developments will make it possible to seamlessly link embedded sensors to any object and quickly accelerate IoT adoption by many sectors. 5G will play an enormous role in enabling smart towns and intelligent homes, enhancing monitoring of assets and logistics, reinventing procedures for industrial production and maintenance and altering other IoT-ready businesses (Humayun et al, 2020;Siriwardhana et al, 2020;Rodriguez et al, 2021aRodriguez et al, , 2021b. The research objectives of this paper are as under: RO1.…”
Section: Research Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further advances in 5G developments will make it possible to seamlessly link embedded sensors to any object and quickly accelerate IoT adoption by many sectors. 5G will play an enormous role in enabling smart towns and intelligent homes, enhancing monitoring of assets and logistics, reinventing procedures for industrial production and maintenance and altering other IoT-ready businesses (Humayun et al, 2020;Siriwardhana et al, 2020;Rodriguez et al, 2021aRodriguez et al, , 2021b. The research objectives of this paper are as under: RO1.…”
Section: Research Objectivesmentioning
confidence: 99%
“…Collaboration between stakeholders in the production and the mobile industry "ecosystems" that have been in significant parallel was crucial to realising Industry 4.0 and 5 G (Khodashenas et al, 2016;Fuentes et al, 2020). The mobile industry traditionally focuses on providing conventional, voice, video and data to consumers, and the production industry relies on its solutions and retrofits to enhance its wireless connectivity within factories, facilities and warehouses from the wireless technologies (Silva and Guerreiro, 2020;Rodriguez et al, 2021aRodriguez et al, , 2021b.…”
Section: Introductionmentioning
confidence: 99%
“…In order to validate its design, the presented novel crosslayer QoS-aware multi-connectivity link selection scheme was implemented. Figure 3 details the functional block diagram of the implementation, which is based on the wireless multi-access gateway (MAGW) with layer-2 tunneling capabilities, previously presented in [16]. This device allows for transparent end-to-end integration of Ethernet-based systems.…”
Section: A Qos-aware Multi-connectivity Scheme Implementationmentioning
confidence: 99%
“…They demonstrated that information latency is more critical in 5G vertical applications than in conventional URLLC. Rodriguez et al [2021] presented an experimental framework which consist on the use and performance optimization of 5G-integrated autonomous mobile robots. They used prototyping tools consisting of a network traffic sniffer, a 5G emulator, and a wireless multi-access gateway.…”
Section: Related Workmentioning
confidence: 99%